Implementasi Algoritma Rabin-Karp Untuk Pendeteksian Plagiarisme Pada File Dokumen Berupa Text Berbasis Web - Aldian Aldian; Mubarak Mubarak (Journal of Information System Research (JOSH), 2022)
Plagiarism is always in the spotlight, not least in the academic sector both from school to college level. Therefore, prevention and early detection need to be done to minimize this plagiarism action. There are several methods that can be implemented, one of which uses the Rabin-Karp algorithm. Rabin-Karp algorithm is one of the string matching, algorithms that can be used to measure the level of similarity of text. The thesis aims to design and build an application using the Rabin-Karp algorithm to find the percentage of similarities in two document files in the form of tested text. According to the results of tests conducted by (Priambodo, 2018) between the original document and the document tested from the test results of 10 text documents using the Rabin-Karp algorithm, resulting in the largest accuracy rate of 47.58%. While the smallest accuracy rate is 19.28%. While the results of the analysis conducted from 10 documents tested with a value of k-gram 1, have obtained the largest percentage of similarity, which is 57.14% and the smallest at 28.57%. Where if the similarity value <30% is included in mild plagiarism, 30%-70% moderate plagiarism and >70% large plagiarism.